REMOVAL OF METHYLENE BLUE FROM AQUEOUS SOLUTION USING ACTIVATED RICE HUSK BIOCHAR: ADSORPTION ISOTHERMS, KINETICS AND ERROR ANALYSIS - Nworie, F. S; Nwabue, F.I; Oti, W.; Mbam, E; Nwali, B.U (Journal of the Chilean Chemical Society, 2019)
Removal efficiency of methylene blue (MEB) from aqueous media was studied under different experimental conditions of pH, contact time and initial concentration of the adsorbate. Activated rice husk biochar (ARHB) was characterized using BET surface area and XRD. The XRD diffraction indicated amorphous nature of the biochar with pore size (cc/g) and pore surface area (m2/g) of 9.369 and 27.32 respectively from BET surface area plot. Equilibrium isotherm based on coefficient of non- determination indicated the following order as best fit model: Hill ˃ Kiselev ˃Elovic ˃Flory-Huggins > Langmuir > Jovanovic > Harkin-Jura >Freundlich > Henry > Temkin >Redlich Peterson>Durbinin-Kaganer Redushkevich >Hill–de Boer > Fowler–Guggenheim. Based on the highest correlation coefficient and the lowest values of the error functions applied to the kinetic models, Weber and Morris intra-particle diffusion and liquid film diffusion were noted to be in control of the sorption rate. The MEB sorption capacity of the activated biochar was 356.99 mmolkg-1 which was in the range of commercially available activated carbons and other biosorbents.